Universalization of Stereotypical Representation and Subjugation of Women in The Waste Land - Gyawali, Ramesh (English Language Teaching Perspectives, 2024)
The Waste Land deals with the issues of subjugation and stereotypical representation of women with the strategy of universalization. Furthermore, it endeavors to reveal female oppression by making surprising connections between the present with the past through myth and allusions, which serves the purpose of universalizing the issue of the subjugation of women. This study addresses the gap in exploring the domination and negative representation of women as being similar regardless of differences in time, place, age, and class. This study aims at revealing the hitherto biased and dominating attitude of society towards women. The research employed a qualitative approach combining textual analysis with Critical Discourse Analysis approach. The Waste Land was selected purposefully for data collection and analysis. Data related to the subjugation and negative representation of women were collected and coded as modern wastelanders, ancient wastelanders, and the way of subjugation of women to develop the broad theme of the strategy of universalization, and characters and types to contribute to formulating the theme of stereotypical representation to address the issues of the research. Coded data were analyzed making comparisons and contrast and word choices as nouns, verbs, and adjectives with others were approached through Critical Discourse Analysis. The findings indicate that the women in the poem, irrespective of classes and categories ranging from ancient to modern days, are stereotypically represented and subjugated. The results suggest that the use of mythical and allusive techniques and conscious choice of lexicon may contribute to the exploration of hegemony, oppression, and negative representation.